Diabetic Cardiomyopathy: Current Approach and Potential Diagnostic and Therapeutic Targets - Georgiana-Emmanuela Gilca; Gabriela Stefanescu; Oana Badulescu; Daniela-Maria Tanase; Iris Bararu; Manuela Ciocoiu (Journal of Diabetes Research)
Although ischemic heart disease is the major cause of death in diabetic patients, diabetic cardiomyopathy (DCM) is increasingly recognized as a clinically relevant entity. Considering that it comprises a variety of mechanisms and effects on cardiac function, increasing the risk of heart failure and worsening the prognosis of this patient category, DCM represents an important complication of diabetes mellitus, with a silent development in its earlier stages, involving intricate pathophysiological mechanisms, including oxidative stress, defective calcium handling, altered mitochondrial function, remodeling of the extracellular matrix, and consequent deficient cardiomyocyte contractility. While DCM is common in diabetic asymptomatic patients, it is frequently underdiagnosed, due to few diagnostic possibilities in its early stages. Moreover, since a strategy for prevention and treatment in order to improve the prognosis of DCM has not been established, it is important to identify clear pathophysiological landmarks, to pinpoint the available diagnostic possibilities and to spot potential therapeutic targets.